Review of Vallecillichthys multivertebratum (Teleostei: Ichthyodectiformes), a Late Cretaceous (early Turonian) “Bulldog fish” from northeastern Mexico - Alberto Blanco-Piñón; Jesús Alvarado-Ortega (Revista Mexicana de Ciencias Geológicas)
A complete description of Vallecillichthys multivertebratum Blanco and Cavin, 2003, is provided. This ichthyodectiform fish was collected in the Vallecillo Member of the Agua Nueva Formation (Upper Cretaceous: lower Turonian) at Vallecillo, Nuevo León State, northeastern Mexico. On the basis of a comparative study, this monospecific genus is recognized as member of the suborder Ichthyodectoidei and placed with Ichthyodectes and Xiphactinus into the family Ichthyodectidae. This work provides data on Vallecillichthys for a future comprehensive phylogenetic analysis including all ichthyodectiform species.